Implementasi Sistem Informasi Sederhana Untuk Administrasi Keuangan Posyandu - Ahmad Rifa’i; Ahmad Faqih; Fadli Iqbal Syaidin; Fatkhan Mubarok (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This community service program aims to assist Posyandu (Integrated Health Service Post) in improving the efficiency and transparency of financial administration through the implementation of a simple information system. The main problems faced by the Posyandu partners are the use of manual recording in financial management, the low level of digital literacy among the cadres, and the lack of transparency in preparing financial reports. These conditions can lead to recording errors, loss of financial data, and reduced trust from the community and donors. Therefore, the solution offered in this activity is the development and implementation of a simple digital-based information system to help record income, expenses, and automatically generate financial reports. The method of implementing this activity includes identifying the needs of partners, system design, training and assisting Posyandu cadres, as well as evaluating the effectiveness of the system usage. The results of the activity showed that Posyandu cadres were able to independently use the information system to record financial transactions and prepare standardized financial reports more quickly, accurately, and transparently. In addition, the implementation of this program also improved the digital literacy of cadres and facilitated the financial accountability process to the government and donors. The outcomes of this activity include a simple financial administration information system based on Google Sheets or automated Excel, user manuals, and standardized financial report templates. This program is expected to be a sustainable solution for Posyandu in managing financial administration more effectively and efficiently, while also enhancing the professionalism of Posyandu in providing health services to the community. With this system, Posyandu will not only be better prepared to manage existing funds but will also find it easier to gain trust from external parties for the sustainability of community health programs.